Evolution of structural neuroimaging biomarkers in a series of adult patients with Niemann-Pick type C under treatment. Issue 1 (December 2017) - Masingue, Marion; Adanyeguh, Isaac; Nadjar, Yann; Sedel, Frédéric; Galanaud, Damien; Mochel, Fanny
Abstract Background Niemann-Pick type C (NPC) disease is a lysosomal storage disorder characterized by a wide clinical spectrum and non-specific conventional magnetic resonance imaging (MRI) signs. As substrate reduction therapy with miglustat is now used in almost all patients, its efficacy and the course of the disease are sometimes difficult to evaluate. Neuroimaging biomarkers could prove useful in this matter. We first performed a retrospective analysis of volumetric and diffusion tensor imaging (DTI) data on 13 adult NPC patients compared to 13 controls of similar age and sex. Eleven NPC patients were then studied using the same neuroimaging modalities over a mean of 5 years. The NPC composite score was used to evaluate disease severity. Results NPC patients showed atrophy in basal ganglia – pallidum (p  = 0.029), caudate nucleus (p  = 0.022), putamen (p  = 0.002) and thalamus (p  < 0.001) – cerebral peduncles (p  = 0.003) and corpus callosum (p  = 0.006), compared to controls. NPC patients also displayed decreased fractional anisotropy (FA) in several regions of interest – corona radiata (p  = 0.015), internal capsule (p  = 0.007), corpus callosum (p  = 0.032) and cingulate gyrus (p  = 0.002) – as well as a broad increase in radial diffusivity (p  < 0.001), compared to controls. Over time, 3 patients worsened clinically, including 2 patients who interrupted treatment, while 8 patients remained stable. With miglustat, no significant volumetric change was observed but FA improved after 2 years in the corpus callosum and the corona radiata of NPC patients (n  = 4;p  = 0.029) – although that was no longer observed at further time points. Conclusion This is the first study conducted on a series of adult NPC patients using two neuroimaging modalities and followed under treatment. It confirmed that NPC patients displayed cerebral atrophy in several regions of interest compared to controls. Furthermore, miglustat showed an early effect on diffusion metrics in treated patients. DTI can detect brain microstructure alterations caused by neurometabolic dysfunction. Its potential as a biomarker in NPC shall be further evaluated in upcoming therapeutic trials.